"Class smoke-free" pledge impacts on nicotine dependence in male adolescents: A cluster randomized controlled trial. (1st November 2016) - Al-sheyab, Nihaya A.; Alomari, Mahmoud A.; Shah, Smita; Gallagher, Robyn
Abstract: Objective : To test the effectiveness of a school-based, peer-led smoking and asthma education program with an additional "class smoke-free" pledge on smoking-related knowledge and perception, nicotine dependence, and asthma control in male high school students in Jordan 4 months post-intervention. Methods : In this cluster-randomized controlled trial, four male schools in Irbid, Jordan, were randomly assigned to the intervention ( n = 215) or comparison ( n = 218) groups. Trained educators trained senior students from the four schools to be peer leaders ( n = 53), who then taught peers in grades 7 and 8 ( n = 433). The peer leaders in the intervention schools implemented the smoke-free pledge within the 7th and 8th graders, who voluntarily signed the pledge for 4 months. The comparison group received the same intervention components as the intervention group, minus the smoke-free pledge. Data were collected from students in grades 7 and 8 at baseline and 4 months post-intervention. Results : Students from the intervention group reported significant improvements in smoking-related knowledge and perception and lower nicotine dependence as compared to the comparison group. Improvement in asthma control was greater in nonsmokers versus smokers. Conclusions : Voluntary group commitment smoke-free through a pledge is an incentive to motivate adolescents to abstain from smoking. Using social influences approaches in schools is useful in countering current aggressive tobacco marketing campaigns in Arab youth.